Phytosociological analysis of the aquatic vegetation of the main Greek freshwater lakes. Poster presentation in 11th Symposium for European Freshwater Sciences. Zagreb, June 30 – July 5, 2019 - D. Zervas; I. Tsiripidis; Tsiaoussi, V. (2019)
Έργο "Παρακολούθηση λιμνών"